Spermine Regulates Immune and Signal Transduction Dysfunction in Diabetic Cardiomyopathy - Wei, Can; Sun, Mengting; Liang, Xiao; Che, Bingbing; Wang, Ningning; Shi, Lili; Fan, Ying (Frontiers in Endocrinology, 2022)
Background: Diabetic cardiomyopathy (DCM) is a specific form of cardiomyopathy that is independent of coronary artery disease and hypertension. Exploring the transcriptomics of DCM is of great significance for understanding the biology of the disease and for guiding new therapeutic targets for the potential therapeutic effect of spermine (SPM). Methods and Results: By using a mouse DCM model, we analyzed the transcriptome of the myocardium, before/after treatment with SPM. Using RNA sequencing (RNA-seq), we identified 1318 differentially expressed genes (DEGs) with 636 being up-regulated and 683 being down-regulated in DCM compared to control check (CK). We then identified 1393 DEGs with 887 being up-regulated and 506 being down-regulated in SPM compared to DCM. Kyoto Encyclopedia of genes and genomes (KEGG) analysis demonstrated that the DEGs were significantly enriched in immune system and signal transduction related pathways. UpSet Venn analysis showed that 174 DEGs in DCM could be reversed by SPM, with 45 candidates related to immune system and related signal transduction pathways. Trend analysis demonstrated the dynamic changes of gene levels in DCM and SPM treatment, shown as 49 immune and signal transduction related candidates were significantly enriched in some classical pathways, such as Complement and coagulation cascades, Phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-protein kinase B (Akt) signaling pathway. To further reveal the protective mechanism of SPM to DCM, we predicted 14 overlapped transcription factors (TFs) and their co-factors involved in gene transcription regulation, and showed gene interaction with Cytoscape. Conclusion: The biomarkers and canonical pathways identified in this study may hold the key to understanding the mechanisms of DCM pathobiology and providing new targets for the therapeutic effect of SPM against DCM by targeting abnormal immune response and signal transduction.